Long-standing motor and sensory recovery following acute fibrin sealant based neonatal sciatic nerve repair - Biscola, Natalia Perussi [UNESP]; Cartarozzi, Luciana Politti; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP]; De Oliveira, Alexandre Leite Rodrigues (Hindawi, 2016)
Brachial plexus lesion results in loss of motor and sensory function, being more harmful in the neonate. Therefore, this study evaluated neuroprotection and regeneration after neonatal peripheral nerve coaptation with fibrin sealant. Thus, P2 neonatal Lewis rats were divided into three groups: AX: sciatic nerve axotomy (SNA) without treatment; AX+FS: SNA followed by end-to-end coaptation with fibrin sealant derived from snake venom; AX+CFS: SNA followed by end-to-end coaptation with commercial fibrin sealant. Results were analyzed 4, 8, and 12 weeks after lesion. Astrogliosis, microglial reaction, and synapse preservation were evaluated by immunohistochemistry. Neuronal survival, axonal regeneration, and ultrastructural changes at ventral spinal cord were also investigated. Sensory-motor recovery was behaviorally studied. Coaptation preserved synaptic covering on lesioned motoneurons and led to neuronal survival. Reactive gliosis and microglial reaction decreased in the same groups (AX+FS, AX+CFS) at 4 weeks. Regarding axonal regeneration, coaptation allowed recovery of greater number of myelinated fibers, with improved morphometric parameters. Preservation of inhibitory synaptic terminals was accompanied by significant improvement in the motor as well as in the nociceptive recovery. Overall, the present data suggest that acute repair of neonatal peripheral nerves with fibrin sealant results in neuroprotection and regeneration of motor and sensory axons.